Moving Beyond Metabolic Encephalopathy: An Update on Delirium Prevention, Workup, and Management - Brown, Ethan G.; Douglas, Vanja C. (Seminars in Neurology, 2015)
Delirium is a condition that frequently complicates hospitalization and consists of an acute decline in orientation and attention, often accompanied by other cognitive changes. Delirium is tied to multiple detrimental outcomes both in the short and long term, including cognitive and functional decline, inpatient complications, and mortality. Postoperative, elderly medical, and critical care patients have been identified as populations at particular risk. In this review, the authors discuss current theories on pathophysiology, recommended workup, and evidence-based prevention and management of inpatient delirium. In general, instituting a system of active screening of at-risk populations and nonpharmacologic interventions for prevention and treatment seems to be the most effective method of addressing delirium. More research is needed to clarify the etiology of delirium and develop safe therapeutic options that address the underlying pathophysiology.
Keywords: delirium; attention; inpatient; elderly